INTEGRATING FINANCIAL STABILITY AND CUSTOMS COMPLIANCE INDICATORS INTO A COMPOSITE RATING FRAMEWORK FOR FOREIGN TRADE ENTERPRISES (International Congress on Economics, Management and Business Studies, 2026)
This article develops a research about developing stability-rating system in Uzbekistan with some foreign trade indicators. The central argument is that the economic condition of a business entity engaged in foreign trade cannot be assessed solely through conventional financial ratios. Liquidity, financial independence, profitability, efficiency, and cash-flow indicators remain indispensable, but they must be complemented by customs-specific indicators that reflect the legality, discipline, and sustainability of external trade operations. The article therefore proposes a composite approach in which traditional financial coefficients are integrated with quantitative, qualitative, and dynamic foreign-trade metrics, customs-audit outcomes, and localized diagnostic thresholds.
Keywords: Financial stability, customs compliance, post-clearance audit, import analysis, risk scoring, stability rating, Beneish M-Score, Altman Z''-Score, declaration-based indicators, foreign trade discipline.